STRATEGI PENGELOLAAN KELAS DALAM MENINGKATKAN KUALITAS INTERAKSI GURU DAN SISWA DI SMP WIJAYA KUSUMA BANJAR MARGO - Alfu Arifin; Apri Eka Budiyono; Ahmad Dawam (STKIP Pesisir Selatan, 2026)
This study aims to analyze the classroom management strategies implemented at Wijaya Kusuma Banjar Margo Junior High School in improving the quality of teacher-student interactions. Effective classroom management is essential for creating a dynamic and conducive learning environment that encourages active student participation. This study uses a qualitative approach with a case study method to explore classroom management practices and their impact on the quality of interaction. Data were collected through classroom observation, interviews with teachers, students, and the principal, as well as documentation analysis. The findings show that flexible classroom physical arrangements, the implementation of clear classroom rules, and empathetic two-way communication between teachers and students play a major role in increasing student engagement. However, the main challenges faced are limited technological resources, large class sizes, and a lack of specific training on innovative classroom management. Based on these findings, the recommendations proposed include improving technological resources, providing ongoing training for teachers, and implementing more consistent active learning methods. This study contributes to the development of more effective classroom management in improving teacher-student interactions in secondary schools.